Systematic study of Chinese Acroclita Lederer (Lepidoptera: Tortricidae), with the description of a new species - Zhang, Aihuan (Zootaxa, 2023)
Five species of Acroclita Lederer, 1859 are reported from China, including Acroclita ovata sp. nov., which is described and illustrated from Hubei Province. The previously described species are listed along with references cited, host-plants, specimens examined, and distributions. A taxonomic key to Chinese species of Acroclita is presented based on characters of the male genitalia.